Unfair play in World Cup qualification? An analysis of the 1998–2010 FIFA World Cup performances and the bias in the allocation of tournament berths. (2nd January 2016) - Stone, Christian; Rod, Michel
Abstract : This paper reviews the FIFA World Cups 1998–2010 with data available from the FIFA website and assesses the performance of each region in relation to the number of World Cup qualifications spots that the region is awarded. We raise the issue of whether FIFA should be more concerned with the participation of more members from its federations in the World Cup than the financial gain from doing so. Our non-econometric analysis illustrates that the current allocation may be resulting in the awarding of qualification spots to teams that if not unfair, certainly warrants discussion. We seek to demonstrate that the current system of qualification is based neither on ensuring the qualification of the best 32 teams in the world, nor does it fairly allocate qualification spots on the number of teams per federation or any other metric. We conclude with a plea for more transparent allocation processes.